METHODOLOGICAL BASICS OF SCIENTIFIC COGNITION OF ECONOMIC PROCESSES - HRYTSYNA, LESIA; KHARUN, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the article is to determine the methodological fundamentals of scientific cognition of economic processes. The content of scientific cognition was defined to achieve this purpose. Also, the connection between scientific cognition and the basic elements of research methodology of economic processes was determined.The research results showed that scientific cognition of economic processes is a special type of human cognitive activity characterized by objectivity, reliability, and validity of the results. The main functions of scientific cognition are the following: description, explanation, understanding, prediction. The purpose of scientific cognition is due to the practical and theoretical needs of knowledge system development.The process of scientific cognition is impossible without determining the methodological basis of economic research. To reveal the content of the methodology of scientific cognition of economic processes, we proposed to present it in vertical and horizontal planes, using hierarchical and pluralistic approaches. The first approach (hierarchical) defines a clear hierarchical (multilevel) structure of the methodology of scientific knowledge. As a result, the methodology can be represented as a three-level object consisting of philosophical (fundamental) methodology, methodology of individual science, and research methodology. The second approach (pluralistic) defines the essence of methodology as a set of concepts, categories, principles, methods, techniques, laws, and patterns. We defined the content of the basic elements of methodological foundation, such as concept, category, and principle. Analysis of the meaning of terms concept and category allowed to prove the need for their distinction. The separation criteria between the categories and notions as the forms of human thinking were discovered. The category is a concept that reflects the most general connections and relations existing in society. Considering the essence of the term principle, we identified its logical connection with such concepts as idea, position, value, standard.
Keywords: methodology; scientific cognition; principle; concept; category; economic process